Pendampingan Strategi Pemasaran dan Pelabelan Jamu Tradisional "Sehat Sentosa" - Rahmawati, Lilis; Barid Nizarudin Wajdi, Muh.; Saini, M; Ali Fauzi, M.; Anwar, Zainul (Bisma : Bimbingan Swadaya Masyarakat, 2024)
Herbal drinks are an Indonesian cultural heritage made from various spices and have health benefits such as refreshing the body, accelerating metabolism, and increasing appetite. UMKM "Jamu Sehat Sentosa" is one of the home industries that supplies herbal medicine around Balonggebang. However, most herbal medicines are still sold using bottles only without adding labels which of course are less attractive to consumers. This service aims to provide assistance related to good and attractive marketing and labeling, so that it can guarantee the quality of herbal medicine product packaging so that it can increase economic competitiveness. Service is carried out using two methods, namely lectures and training. The lecture method is carried out at the beginning to provide an understanding of how to market suitable products. Furthermore, the training method is carried out for the production process, packaging selection, packaging process, and labeling design. Assistance has been carried out, In the production process, attractive herbal medicine product packaging is labeled. for the sale of herbal medicine, it is packaged in 500ml bottles and labels are added to each bottle. Consumer appeal testing is carried out by comparing the results of herbal medicine sales using old and new packaging. Based on the test results, it shows that the new packaging is more in demand by consumers than the old packaging. Based on the survey, it is known that consumers prefer products with new packaging and labels because they are more attractive, safe and informative.